Etnomatematika: Eksplorasi Konsep Geometri Pada Bangunan Masjid Muhammad Cheng Hoo Purbalingga - Latifah Fitriana Rahmah; Kusno, Kusno (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
There is a big difference between the mathematics problems taught in school and the mathematics that exists in society. As a result, educators face difficulties in modeling formal mathematical concepts with mathematical problems that occur in everyday life. By connecting mathematics learning with culture it will help the learning process. This will make it easier for educators to understand the topics being studied because they are relevant to everyday life. The aim of this research is to explore the concept of geometry in the Muhammad Cheng Hoo Purbalingga mosque. Data collection methods use interviews, observation and documentation. The camera is the tools and materials used. The data presentation is given in the form of images, along with a description of the ethnomathematics values that exist in the mosque. This research shows that the Muhammad Cheng Hoo Mosque in Purbalingga combines three cultural elements, namely Chinese, Arabic and Javanese. The results of this research show that the Muhammad Cheng Hoo mosque contains geometric elements, namely flat shapes, spatial shapes and transformations. This research is recommended for use as mathematics learning material. Keywords: Mathematics, Ethnomathematics, Muhammad Cheng Hoo Mosque